Gender bias in education opportunities for population aged 12-18 in Mexico: 1992-2004 - Aguayo Téllez, Ernesto; Chapa Cantú, Joana Cecilia; Rangel González, Erick; Treviño Villarreal, María de Lourdes; Valero Gil, Jorge Noel (2008)
There is considerable evidence that resources are not allocated randomly within households, and that resources are unequally distributed within the family in many developing countries. Such an unequal distribution of goods usually takes the form of a bias against females. For example, girls lag markedly behind boys in schooling in many developing countries even though this gender gap has been declining in recent years. Using an OLS-Robust model and a ML-Random Effects model for the years 1992, 1998 and 2004 of ENIGH, we did not find enough statistical evidence to support the idea that poor families, nether in rural nor in urban areas, provide more education to their 12 to 18 years old sons or daughters. In fact, contrary to the common belief, we found that non-poor families, invest more in the education of their daughters, especially in the urban areas. However, this education discrimination against male children has been decreasing over the years. It is also found that female head of households are more likely to have children with higher levels of schooling and that children having both parents at home or having older brothers or sisters present higher levels of educational attainment